The role of family functioning: How the Big Five affect metacognitions about smartphone use - Xie, Yuntian; Lei, Qian; Xie, Ruotong; Yang, Yaping (Frontiers in Psychology, 2022)
The present study aimed to explore the relationship between the Big Five and metacognitions about smartphone use and the mediating role of family functioning. A cohort of 470 Chinese college students was selected as subjects based on the second edition of the Big Five Inventory-2, the Chinese version of the Metacognitions about Smartphone Use Questionnaire, and the general functioning subscale of Family Assessment Device. The results showed that only neuroticism was significantly and positively correlated with positive metacognition, while the correlation between other personality traits and positive metacognition was not statistically significant. Except for openness, the correlation between other personality traits and negative metacognition was statistically significant. In addition, conscientiousness, extraversion and neuroticism were found to directly affect negative metacognitions about smartphone use and indirectly affect the negative metacognitions about smartphone use through family functioning. Findings provide insights into the design of interventions aimed at improving metacognitions about smartphone use and preventing smartphone addiction among college students.